Focal Task-specific Dystonia among Professional Musicians in Latin America. (3rd February 2015) - Gatto, Emilia; Chade, Anabel; Persi, Gabriel; Parisi, Virginia; Ayarza, Ana; Campuzano, Miguel; García, Silvia
In Response To: Frucht SJ. Focal task-specific dystonia—from early descriptions to a new, modern formulation. Tremor Other Hyperkinet Mov. 2014; 4. doi:10.7916/D8VD6WHP